First Sustainable Aziridination of Olefins Using Recyclable Copper-Immobilized Magnetic Nanoparticles - Khodadadi, Mohamad Reza; Pourceau, Gwladys; Becuwe, Matthieu; Wadouachi, Anne; Toumieux, Sylvestre (Synlett, 2019)
The first copper-catalyzed aziridination of olefins using recyclable magnetic nanoparticles is described. Magnetic nanoparticles were modified with dopamine and used as a support to coordinate copper. The methodology was optimized with styrene as olefin and using [N-(p-toluenesulfonyl)imino]phenyliodinane (PhI=NTs) as nitrene source. A microwave irradiation decreased the reaction time by 4-fold compared to conventional heating method. The catalyst was recovered by simple magnetic extraction and could be reused successfully up to five times without significant loss of activity. The methodology was applied to a range of different olefins leading to moderate to excellent yields in the formation of the expected aziridine.
Keywords: sustainable aziridination; magnetic nanoparticle; copper catalyst; nitrene insertion